STRENGTHENING DIGITAL GOVERNANCE IN THE IMPLEMENTATION OF DIGITAL POPULATION IDENTITY IN RIAU PROVINCE, INDONESIA - Indrian Syafitri,; Resti Hefriyenni,; Nurman,; Annisa Mardatillah, (Proceeding International Conference on Social Sciences, 2026)
The transformation of public administration in the digital era demands robust digital governance to ensure effective, transparent, and inclusive service delivery. This study examines the implementation of the Digital Population Identity (IKD) program in Riau Province, Indonesia, as a strategic effort to enhance administrative efficiency and strengthen digital public management. Using a qualitative descriptive approach, data were collected through interviews, document analysis, and observation of local government institutions responsible for population administration. The findings reveal that while the adoption of digital identity systems has improved data integration and service accessibility, several governance challenges persist, including limited digital literacy among civil servants, inadequate technological infrastructure, and fragmented institutional coordination. Strengthening digital governance through capacity building, standardized data management, and clear regulatory frameworks emerges as a key determinant of successful digital identity implementation. This study underscores the importance of aligning technological innovation with governance reform to ensure that digital transformation contributes to public service efficiency, accountability, and citizen trust. The results provide practical insights for policymakers and local governments in developing countries seeking to optimize e-government initiatives through integrated and sustainable digital governance strategies.